Regeneration of Activated Carbon Sutured Hexavalent Chrome - Elmerzouki, K.; Bimaghra, I.; Khalidi, A. (Journal of Applied Solution Chemistry and Modeling, 2021)
In order to prevent a simple pollution transfer and for the purpose of valorization of the process of activated carbon treatment, this one, saturated with pollutants should not increase the pollution mass of household waste. Indeed, an adsorbent offers a real interest only if it can be easily regenerated. This work addresses to the becoming the activated carbon after being saturation with hexavalent chromium. The activated carbon should not be stored directly, since the acid rain waters might leach some heavy metals. This would contaminate the soil and water resources. For this, it should be treated after use and returned to its original structure and chemical composition for an eventual future use with a good yield of re-adsorption. Within this work, the use of a base (KOH) has recovered an amount of hexavalent chromium retained by the activated carbon CAB. This one, regenerated was again used to secure the hexavalent chromium ions during several cycles. Regeneration test results have shown that the efficacy of CAB remains almost constant during the first four cycles of reuse and then decreases during the fifth cycle.